Cover page, CONTENTS, List of figures, List of tables (Discussion Papers, 2012)
The research programme commissioned by Interreg IIIB CADSES has aimed towards the adaptation of European spatial development strategies, as well as the integrated definition of environmental and spatial development objectives of in the economic, cultural and ecological problem areas of the Carpathian territory. This plays a role in strengthening protection for the territory’s natural resources, and, through encouraging cohesion and the preservation of natural and cultural heritage, its deeper internal and European integration. In addition to defining the tools of development policy, a medium-term development strategy (Visions and Strategies in the Carpathian Area) has been prepared, integrating analyses and studies created in other segments of the research project. In the framework of the research, a broad socio-economic analysis was prepared on the region’s situation (Socio-Economic Analysis of the Carpathian Area); prior development programmes in the Carpathians and their lessons were considered in the evaluation of current plans, concepts and programmes; and finally, a broad strategy for the project area was developed.